Impact of China's economic reforms on Singapore trade competitiveness. - Ng, Allan Kim Hee. (2008)
This paper uses shift-share analysis to examine the impact of China’s economic reforms as well as the Asian Financial Crisis on Singapore’s trade competitiveness.